Impact of social disadvantages in the presence of diabetes at old age - María Fernanda Carrillo-Vega; Cidronio Albavera-Hernández; Ricardo Ramírez-Aldana; Carmen García-Peña (BMC, 2019)
Abstract Background Social disadvantages that start during childhood and continue into the later stages in life may be linked to the presence of diabetes during adulthood. Objective. To analyze whether the presence of social disadvantages in childhood and in the present affects the presence of diabetes in older adults. Methods The present study was based on longitudinal data from the third and fourth Mexican Health and Aging Study (MHAS) waves (2012 and 2015). Data on diabetes diagnosis, past (e.g. "no shoes during childhood") and present (e.g. self-perception of economic status) social disparities, and other covariables were analyzed. Results From 8,848 older adults, 21.5% (n = 1903) were classified as prevalent cases (PG), 5.2% (n = 459) as incident cases (IG) and 77.4% (n = 6,486) were free of disease (NDG). The predictor variable "no shoes during childhood" was statistically significant in the model incident versus no diabetes group. Hypertension and body mass index (BMI) were the most relevant covariates as they were statistically significant in the three groups (PG, IG and NDG). Conclusions Not having shoes during childhood, an indicator of social disadvantages, is associated with the incidence and prevalence of diabetes in older adults. This suggests that social disadvantages can be a determinant for the presence of chronic diseases in adulthood.